Perancangan Sistem Informasi Deteksi Penyakit Daun Padi Menggunakan Metode Agile - Faruq Aziz; Daniati Uki Eka Saputri; Nurul Khasanah; Taopik Hidayat (Program Studi Teknik Informatika Universitas Pamulang, 2025)
The development of a rice leaf disease detection information system using the Agile method aims to provide an innovative solution for fast and accurate plant disease identification. The system can detect four major rice leaf disease classes: bacterial blight, brownspot, blast, and healthy conditions. The development process follows an iterative approach, starting from understanding user needs to system implementation and testing. Black-box testing was applied to ensure that all features, such as image upload and disease classification, function according to specifications. Evaluation results indicate that the system achieves high accuracy in disease detection based on the utilized dataset. However, dataset limitations and testing scenarios pose challenges for generalizing results to real-field conditions. Hence, intensive evaluation and dataset updates are crucial for future development. With its user-friendly interface, the system is expected to support farmers in improving productivity and efficiency in rice disease detection.